Exploratory and Confirmatory Factor Analysis of the PROMIS Pain Quality Item Bank - Revicki, Dennis A. (2013)
PURPOSE: The assessment of pain sensation and quality is a key component in understanding the experience of individuals with chronic pain. This study evaluated the factor structure of the Patient-reported Outcome Measurement Information System (PROMIS) pain quality item bank. METHODS: As part of the PROMIS project, we developed a pool of 37 pain quality items, based on a review of existing pain questionnaires and development of new items. A Web-based survey was designed and completed by 845 members of the general population and 967 individuals with different types of chronic pain. Exploratory factor analysis (EFA) was conducted on a random split-half sample of the data to examine the factor structure of the 37 PROMIS pain quality items in the general population and in a chronic pain sample. A confirmatory factor analysis was conducted in the holdout sample. RESULTS: The EFA of the pain quality items resulted in comparable six-factor solutions for the general and chronic pain samples: (1) pulling/tugging pain; (2) tingling/numbness pain; (3) sharp/stabbing pain; (4) dull/aching pain; (5) pounding/pulsing pain; and (6) affective pain. The confirmatory factor analysis in the holdout sample supported this factor structure. CONCLUSIONS: Further research is needed to evaluate the psychometric characteristics of the derived scales based on their factor scores.